From Dialectical Imagination to Experimental Imagination: For a Melancholic Explanation of the Subject-World Relation - Barboza Tello, Marco León Felipe (2022)
The dialectical imagination, the poetic imagination and the experimental imagination, are addressed as three types of imagination useful to account for debates and philosophical positions on issues such as "second nature", therapy and poetry in the analytic tradition or the consequences of the empirical turn in more recent times. Once this has been made explicit, dialogues are established with Donald Davidson's approaches to subjective experience and truth, and reference is made to melancholy as an explanatory fold in the subject's relationship with the world.